Application of the Authority of Civil Servant Investigators in Conducting Immigration Criminal Investigations - Syahrin, Muhammad Alvi (Law Research Review Quarterly, 2018)
Article 105 of Law Number 6 of 2011 concerning Immigration, states that Immigration Civil Servant Investigators (PPNS) are authorized as investigators of Immigration offenses carried out in accordance with the provisions. The results of this study are (i) enforcement of immigration law carried out one of them by investigating the perpetrators of violations of the Immigration Act. The process of investigating perpetrators of violations of the Immigration Act is carried out based on the provisions in the Criminal Procedure Code as a lex generalis and the Immigration Act as a lex specialis. In this study, law enforcement has been carried out against participating in the crime of trafficking in blank immigration document / passport documents by providing invalid data or inaccurate information to the Immigration officer to obtain the Republic of Indonesia's travel documents for himself. (ii) in carrying out immigration law enforcement functions there are still obstacles faced by the Immigration PPNS including lack of knowledge, lack of operational funds, lack of public participation in reporting the presence of foreigners in their environment, weak coordination with other legal apparatus and obstacles stemming from factors law.